Studi Eksperimental Sambungan Butt Joint Dengan Metode Friction Stir Welding Menggunakan Material Nylon 6 Poliamida (PA) - Sihotang, Samsul Bahri; Arief, Dodi Sofyan; Dalil, M. (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Friction Stir Welding (FSW) or often called friction welding is one of the mechanical welding methods using friction between the surface of the tool and the surface of the material so that friction occurs and causes heat on the surface of the material for the welding connection process. The friction surface impacts translational motion caused by the rotational pressure of the tool and axial force (forging) to push the friction surface. Retrieval data that will be varied on translational motion speed starting from 12.5 mm / minute, 20 mm / minute and 25 mm / minute. In this study the shape and dimensions of the material used were 100 mm long, 50 mm wide with a thickness of 5 mm while the types of tools used in this study used a type of cylinder with dimensions of 6 mm pin, 25 mm shoulder and 50 mm tool length. In this study the data collection process uses thermal devices and jigs. Where the function of this thermal heater is to lift the temperature of the material that is in accordance with what is needed (melting point). And the function of this jig is to grip or clamp the material on the position of the horizontal milling machine. The purpose of this study was to study the method of pulling welding friction using the Friction Stir Welding (FSW) method on nylon 6 material using the ASTMD-638-IV standard.Keywords : Stir friction welding, weld surface, friction weld, polyamide polymer.